A Model For Moisture Transport In A High-Level Radioactive Waste Repository Drift - S. T. Green; D. B. Walter; R. W. Fedors; F. T. Dodge (Society for Mining, Metallurgy & Exploration, 2004)
Spatial and temporal temperature variations in a high-level radioactive waste repository drift can give rise to moisture transport within the drift. Knowledge of this moisture transport may be important to assessing the potential for corrosion of all metallic components in the drift. The model presented here shows one approach to simulating evaporation, transport, and condensation of water in large underground openings using a framework based on computational fluid dynamics. Simulation results that explicitly model water and latent heat transport are presented.